Congenital heart diseases and pregnancy, Universitary Hospital Center of Gynecology Obstetrical of Befelatanana, Madagascar - Razafindrainibe, Tanjonirina; Rakotonomenjanahary, Sidonie; Andrianirina, Mamitiana; Ravel, Nasolotsiry E. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Congenital heart diseases are malformations formed during the first weeks of life. Thanks to advances in medicine, they could be cared properly and pregnancies on heart diseases could be continued and completed. These malformations are sources of morbidity even high maternal fetal mortality. Whence our motivation to carry out this study and improve its care. Methods: This is a retrospective observational study reporting clinical cases of congenital heart disease pregnancies, only seen at the UHC-GOB over a seven years period (01 February 2007 - 28 February 2014). Results: We have identified 10 cases of congenital heart diseases out of 56 320 deliveries, that is, an incidence of 0.12 per 1000 deliveries. Isolated arterial canal persistence is predominant. The average age is 26±1. Four cases of congenital heart diseases diagnosed and repaired during childhood, have been noted as well as 02 cases of fortuitous discovery during pregnancy. No joint obstetric and cardiac follow up was performed for our patients. Delivery by high way is recommended in 70% of cases which 57% under peridural anesthesia. Half of the patients had peri-gestational cardiac decompensation such as dyspnea, pre-eclampsia and vacuo-shock progressively decreasing in post-partum. On the fetal side, we recorded 01 intra-uterine delayed growths, 03 premature births and 02 deaths. Conclusions: Pregnancy prognosis on congenital heart disease is based on the type of malformation, close follow up and a multidisciplinary care (Gyneco-obstetrician, Cardiologist, Reanimator, Pediatrician and Geneticist.